Manajemen Diabetes Insipidus pada Pasien Meningioma Pascakraniotomi Pengangkatan Tumor di Ruang Rawat Intensif - Wisudarti, Calcarina Fitriani Retno; Jufan, Akhmad Yun; Yuliani, Irma (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2019)
Surgery in the hypothalamic area is often accompanied by disturbances of water, electrolytes, and osmoregulation due to manipulation and vascular changes of the neurohypophysis. Over the last few decades, surgical approaches to craniopharyngioma have been developed. Initially, tumor resection was the treatment of choice but now evolved to minimally invasive surgery such as transphenoidal surgery. We reported a 58 years old female patient with suprasellar meningioma underwent removal tumor craniotomy. Patient was ASA 2 physical status with controlled Diabetes Mellitus type 2 non-obese. The operation was smooth and hemodynamically stable during surgery. Patient underwent post-surgery treatment in the ICU.During monitoring in the ICU, urin output of the patient was more than >2 cc/kgBB/hour. From the resultsof investigations, patient was diagnosed with Diabetes Insipidus. During the 6 days of ICU care, periodicexamination of serum and urin electrolytes and periodic fluid balances for monitoring, as well as the use ofvasopressin as a management of Diabetes Insipidus were conducted periodically. The patient improved after treatment for 6 days in the ICU, with urin output and electrolytes returning to normal without vasopressin.